(3JYdjb Ydi HYV GdeSGFd GdePchQI aj cJGH GdcQI hGdGSWhGfI dCQTejOSs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI Cbhd HYO MeO Gddg hJeLjOg Cfj cfJ ai WdH Gdhbha Ydi HYV GdeSGFd GdePchQI ai cJGH GdcQI hGdGSWhGfI dCQTejOS ReGfkG WhjdkG dcKQI GdGMJjGL Edjg ai GdeWGdH GdTQjaI GdgfOSI s
(3BNQgG (B:s
(3eSGQ dfUa GdbWQ eSGQ HGdJYQja ddeMjW eQHY GdbWQ Edi SWM GdOGFQI s
(3Vef eLehY , JQJjHgG (B: 14s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B207s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs